Livestreaming vs pre-recorded: How social viewing strategies impact consumers' viewing experiences and behavioral intentions. (21st September 2018) - Ang, Tyson; Wei, Shuqin; Anaza, Nwamaka A.
Abstract : Purpose: Marketing researchers currently lack a systematic and empirical understanding of digital social viewing strategies. Drawing on social impact theory, this study aims to investigate if and how firm-initiated digital social viewing strategies (livestreaming vs pre-recorded) influence consumer viewing experiences and consequential behavioral intentions. Design/methodology/approach: A scenario-based experiment was conducted with 462 participants. The study involved social viewing strategies in a new product launch context. Data were analyzed using structural equation modeling. Findings: This study demonstrates that social influence cues (social presence and synchronicity) inherent in a livestreaming strategy induce a more authentic consumer viewing experience than a pre-recorded strategy, which in turn increases consumers' searching and subscribing intention. However, a company's social viewing strategy does not moderate the effect of search and subscribe intention on purchase intention. Research limitations/implications: This study extends the application of social impact theory by showing that social presence and synchronicity impact authentic consumer viewing experiences, which influence consumers' searching, subscribing and purchasing intention. Practical implications: This study validates the importance of using social viewing as a viable digital marketing strategy for practitioners. The paper provides marketers ways to increase consumer purchase intention via livestreaming marketing content, particularly for new products. Originality/value: This study extends the traditional research on social viewing into the realm of digital social viewing. It is among the first to delineate the advantages of both livestreaming and pre-recorded social viewing approaches.